Rasio Profitabilitas: Mengukur Performance dan Tingkat Kesehatan Perbankan yang Terdaftar di BEI Tahun 2020 - Bahri Bahri; Dicky Arnendra Dwi Nugraha (Universitas Winaya Mukti, 2021)
The Covid-19 pandemic in Indonesia is still ongoing to this day causing the performance and health level of banking profitability to decline and the financial condition of the country disrupted. Banking profitability can be seen in the value of Return On Asset (ROA) to see the effectiveness of banking in making profits by utilizing total assets. The study aims to analyze the effect of financial ratios consisting of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Operating Expenditures to Operating Income (BOPO), and Net Interest Margin (NIM) on Return On Asset (ROA) on banking going public listed on the Indonesia Stock Exchange (IDX) during 2020 during the Covid-19 pandemic. The population in this study was 40 banks with 160 data. Data analysis methods use descriptive statistical tests, classical assumption tests, multiple linear regression tests, t-tests, f-tests, and determination coefficient tests. The results of the study proved that partially the variables CAR, LDR, and BOPO had a negative and significant effect on ROA. NIM has a positive and significant influence on ROA. While NPL has no influence and is not significant to ROA in banks registered with IDX in 2020. Simultaneously car, NPL, LDR, BOPO, and NIM variables have a significant effect on ROA. The implications of the results of the study prove that in the time of the Covid-19 pandemic, the condition of banks registered with the IDX is still healthy and meeting the minimum CAR ratio below 8%, meaning that banks still earn profits from the results of credit capital management to customers. The level of insecurity of the number of bad loans is still low and can still overcome. The value of the operating expense ratio of banking operating.